Conditions for Overcoming Discriminatory Affirmations in Modern Society - Milena A. Klenova (Saratov State University, 2020)
The relevance of the study is conditioned by the necessity for formation of theoretical and practical knowledge and technologies that allow to analyze the conditions for overcoming discriminatory affirmations in modern society. The purpose of the research presented in the article is to analyze systematically the conditions for overcoming discriminatory affirmations in modern society. Hypothesis of the study suggests the assumption that in order to identify the conditions for overcoming discriminatory affirmations, a comprehensive study of the conditions of formation is necessary, followed by a search for ways of their transformation. We established that the conditions for formation of discriminatory affirmations include cultural and historical foundations, social environment, mass media, state policy, etc. The following conditions are emphasized: termination of conflict interaction, search for common or similar points of contact of opponents, decrease in the intensity of negative emotions, provision of effective discussion of the problem and choice of an optimal conflict resolution strategy based on the formed discriminatory affirmations. Narrowing the subject field of the study of triggering events, and as a consequence - overcoming discriminatory affirmations through behavior of a person in a conflict situation, will allow us to distinguish two groups: internal and external formation conditions and implementation of discriminatory attitudes. Internal conditions include prejudices, or stereotypes of a cognitive or emotional level, and external ones are real actions in interaction with an outgroup to implement prejudices already formed. A hierarchical system of conditions for overcoming discriminatory affirmations has been formulated, including four main components, where the first link is the formation of sociocultural identity, as an understanding and value of belonging to one's own group; fixation of sociocultural competence as a system of knowledge and ideas about the "Others"; formation of sociocultural values in relation to "others"; formation of sociocultural tolerance, which includes identity, competence and sociocultural values.